Economic factors affecting point-of-sale systems in Saudi Arabia’s food sectors - Alnafissa, Mohamad; Alamri, Yosef; Kotb, Alaa; Aljohani, Emad S. (Frontiers in Sustainable Food Systems, 2025)
This study investigates the influence of various macroeconomic variables on point-of-sale (POS) systems within the restaurant, café, and food & beverage sectors in Saudi Arabia, analyzing trends in both the total number and value of POS transactions from Q1 2016 to Q4 2023. The research utilized path regression analysis, following initial tests that revealed multicollinearity issues in a standard OLS model. The study was based on secondary data from the Saudi Central Bank and the General Authority for Statistics. The results reveal a positive correlation between several factors and POS sales: per capita income, population, the number of POS devices, credit card loan values, and the COVID-19 crisis, with increases in these factors contributing to higher POS sales. Conversely, higher inflation and the implementation of VAT were associated with a decrease in POS sales. These findings align with economic expectations. In terms of relative importance, the variables were ranked based on their impact on POS sales as follows: Population had the most significant influence, contributing 56.64%, followed by the COVID-19 crisis at 17.62%, inflation at 16.67%, credit card loans at 5.95%, per capita income at 1.69%, VAT at 1.26%, and the number of POS devices at 0.18%. The study offers important insights for policymakers and business leaders regarding strategies to support the expansion of cashless transactions and enhance sectoral resilience amid economic fluctuations.